Multi Media for Receptive and Productive Second and Foreign Language Skill Development - Hery Yufrizal (International Conference on Education and Language (ICEL), 2013)
This article discusses the use of multimedia for receptive and pruductive second and forreign language development. The theoretical bases use for the application of multimedia in second language teaching is on the basis of comprehensible input and comprehensible output, two terms which have been discussed and analyzed in second language acquisition research for the last two decades.Use of multimedia in this article is on two types of language skills: receptive and productive skills covering the four language skills listening, reading, speaking, and writing. Practical examples of the use of multimedia is directed toward using it by learners and by teachers as learning faciltators. A wide range of internet use for university students is given in a more detailed perspective.Key words: multimedia, receptive skills, productive skills, internet, comprehensible input and comprehensible output.